Assessing Perceptions of Academic Staff in Using SmartUMS for Teaching and Learning - Salmah Fattah; Siti Hasnah Tanalol; Asni Tahir (Penerbit Universiti Malaysia Sabah, 2014)
The use of educational technologies for teaching and learning has been implemented in many institutions of higher learning. Universiti Malaysia Sabah (UMS) uses Moodle on SmartUMS e-learning platform to deliver academic courses. Every lecturer needs to register their respective courses on SmartUMS to complement face-to-face teaching and learning routine. The purpose of the study was to investigate academic staff’s acceptance and perceptions towards SmartUMS usage in UMS. The findings will contribute to the development of the UMS’s e-learning strategy, providing information on active participations from the lecturers which will enable the most effective use of education technology. Data was collected from all participants of SmartUMS training sessions. A questionnaire was distributed to 86 respondents and statistically analyzed using SPSS statistical package. The findings revealed that lecturers developed positive acceptance and perception towards using SmartUMS. It also concludes that SmartUMS provide value tools for effective interaction between lecturers and students in their teaching and learning activities.